Types of Plasmodium and the Effect of Environmental Factor against Malaria in Manokwari, West Papua (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2018)
Malaria is a disease caused by parasitic protozoa (Plasmodium) carried by a vector of mosquitoes. There are approximately 100 million regions around the world at risk of malaria. One of the endemic areas of malaria in Indonesia is Papua. Manokwari is one of the districts in West Papua that has a high number of malaria patients. The purpose of this study was to investigate mosquitoes Plasmodium parasites, and malaria in West Manokwari District. The research procedure applied initial survey of the place where malaria vector was captured, capturing malaria vector, general environmental measurement, mosquito species identification, plasmodium examination on mosquito of malaria vector, and plasmodium examination on malaria patient. The total sample obtained from 3 areas was 1550 patients and 496 mosquitos with average numbers up to 150 mosquitos per area.The physical environment, including rainfall, temperature, humidity, altitude, and environmental conditions inside and outside the home greatly affected the incidence of Malaria in Manokwari, West Papua. Malaria is a serious health problem in Indonesia. The physical condition of the environment is the main factor influencing it.The results showed that the type of malaria vector found in West Manokwari region comes from two genera namely Culicidae and Anophelidae. Each malaria vector could carry infections from Plasmodium vivax or Plasmodium falciparum. There are two kinds of Plasmodium parasites that infected humans in Manokwari; Plasmodium falciparum and Plasmodium vivax.